The effect of work life balance on job satisfaction moderated by work motivation - Elis Al Fidhdho; Ayu Lucy Larassaty (Institute of Computer Science (IOCS), 2024)
The objectives in this study are 1) to analyze the work life balance variable on job satisfaction, 2) to analyze the work life balance variable on job satisfaction moderated by work motivation variables. This study uses a quantitative approach with a population of employees of PT Cemerlang Plastindo Group. The sampling technique in this study used purposive sampling. The sample used was 48 production employees. Data collection was carried out through a questionnaire. The analysis in this study used Partial Least Square (PLS) with SmartPLS 4.0 software. There are two model specifications used in PLS, namely: outer and inner models. The results of this study found that work life balance has a positive and significant effect on job satisfaction, work life balance moderated by work motivation has a positive and significant effect on job satisfaction at PT Group Cemerlang Plastindo